Resolva: (y2 + 4y - 5) + (-3y2 + 12y - 1).
Soluções para a tarefa
Respondido por
3
Resposta:
= - 2y^2 + 16y - 6
Explicação passo a passo:
= (y^2 + 4y - 5) + (-3y^2 + 12y - 1).
= y^2 + 4y - 5 - 3y^2 + 12y - 1
= y^2 - 3y^2 + 4y + 12y - 5 - 1
= - 2y^2 + 16y - 6
Respondido por
2
Resposta:
= - 2y^2 + 16y - 6
Explicação passo a passo:
= (y^2 + 4y - 5) + (-3y^2 + 12y - 1).
= y^2 + 4y - 5 - 3y^2 + 12y - 1
= y^2 - 3y^2 + 4y + 12y - 5 - 1
= - 2y^2 + 16y - 6
Tamo junto
Perguntas interessantes
Português,
7 meses atrás
Inglês,
7 meses atrás
Administração,
7 meses atrás
Matemática,
7 meses atrás
Química,
1 ano atrás
Português,
1 ano atrás